Macroeconomic Variable Analysis of Crude Oil Consumption in Indonesia for the Period 1983-2023 - Sultan Sultan; Selma Raisaniva Putri (AIBPM Publisher, 2025)
The imbalance between Indonesia’s rising crude oil consumption and declining domestic production poses risks to sustainable economic growth and energy security. This study analyzes the long- and short-run effects of domestic crude oil prices, manufacturing sector value added, and GDP per capita on Indonesia’s crude oil consumption from 1983 to 2023 using the Error Correction Model (ECM), with annual data sourced from BP Statistical Review 2024 and the World Bank 2024. Long-run results indicate that manufacturing value added (p = 0.0000) and GDP per capita (p = 0.0000) significantly influence crude oil consumption, while domestic crude oil prices (p = 0.6800) are insignificant. In the short run, all three variables significantly affect consumption (p 0.05), with domestic crude oil prices and GDP per capita exerting positive effects and manufacturing value added exhibiting a negative effect. The error-correction coefficient of –0.2643 indicates a moderate adjustment toward long-term equilibrium. These findings demonstrate that economic growth and industrial value creation are primary drivers of energy demand, whereas price mechanisms remain less effective under government subsidies. Policy recommendations include enhancing energy efficiency, promoting industrial modernization, restructuring fuel-subsidy allocations, and investing in renewable energy to reduce oil dependence and support sustainable growth.